COMPARATIVE ANALYSIS OF THE EFFECTIVENESS OF OFFENSIVE AND DEFENSIVE ACTIONS IN WOMEN'S FOOTBALL IN UZBEKISTAN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the effectiveness of offensive and defensive tactics in Uzbekistan's women's football teams (using the example of the Higher League and the national team). During the study, the technical and tactical indicators (TTA) of the 2022-2024 Uzbekistan Women's Championship matches were analyzed. The results show that in modern women's football, the systems of "fast counterattack" and "zonal defense" directly affect the outcome of the game in 65% of cases. At the end of the study, recommendations were provided for adapting the physical fitness of female football players to tactical schemes.